2015
DOI: 10.1017/jfm.2015.245
|View full text |Cite
|
Sign up to set email alerts
|

Budgets of turbulent kinetic energy, Reynolds stresses, variance of temperature fluctuations and turbulent heat fluxes in a round jet

Abstract: The self-preserving region of a free round turbulent air jet at high Reynolds number is investigated experimentally (at x/D = 30, Re D = 1.4 × 10 5 and Re λ = 548). Air is slightly heated (20 • C above ambient) in order to use temperature as a passive scalar. Laser doppler velocimetry and simultaneous laser doppler velocimetry-cold-wire thermometry measurements are used to evaluate turbulent kinetic energy and temperature variance budgets in identical flow conditions. Special attention is paid to the control o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 52 publications
4
58
0
Order By: Relevance
“…Thiesset et al (2014) reported values of A calculated with (3.1) using the data of Friehe et al (1971), Burattini et al (2005b) and Mi et al (2013) and obtained 39.7, 32.7 and 33.5 respectively, which are in quite good agreement with our calculated value. Using the data of Darisse et al (2015), we found that A = 41 when calculated with (3.1), while the experimental estimate is approximately 42. Finally, using the correction of proposed by Darisse et al (2015), we also calculated A based on (3.1) for the data of Panchapakesan & Lumley (1993) and Hussein, Capp & George (1994) and found 34.8 and 38.8 respectively.…”
Section: Resultsmentioning
confidence: 79%
See 4 more Smart Citations
“…Thiesset et al (2014) reported values of A calculated with (3.1) using the data of Friehe et al (1971), Burattini et al (2005b) and Mi et al (2013) and obtained 39.7, 32.7 and 33.5 respectively, which are in quite good agreement with our calculated value. Using the data of Darisse et al (2015), we found that A = 41 when calculated with (3.1), while the experimental estimate is approximately 42. Finally, using the correction of proposed by Darisse et al (2015), we also calculated A based on (3.1) for the data of Panchapakesan & Lumley (1993) and Hussein, Capp & George (1994) and found 34.8 and 38.8 respectively.…”
Section: Resultsmentioning
confidence: 79%
“…Using the data of Darisse et al (2015), we found that A = 41 when calculated with (3.1), while the experimental estimate is approximately 42. Finally, using the correction of proposed by Darisse et al (2015), we also calculated A based on (3.1) for the data of Panchapakesan & Lumley (1993) and Hussein, Capp & George (1994) and found 34.8 and 38.8 respectively. While relatively small, the variation of the analytical values between these experiments is likely to reflect the differences in initial conditions, which certainly affect the experimental estimates of R, A U and A I (e.g.…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations